Adhesive tape
The adhesive tape, featuring a flat yarn cloth substrate and an adhesive layer with specific crosslinkers and a high gel fraction, addresses the challenge of achieving high flame retardancy and adhesive strength, particularly for construction uses.
Patent Information
- Application Number
- JP2021159655
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-09-29
AI Technical Summary
Existing adhesive tapes struggle to achieve high flame retardancy without compromising adhesive properties, especially when the flame retardant is added to the adhesive layer rather than the substrate.
An adhesive tape with a substrate made of flat yarn cloth and an adhesive layer containing an acrylic resin, an isocyanate crosslinker, and an epoxy crosslinker, with a gel fraction of 50 to 80% by mass, which enhances both flame retardancy and cutting properties.
The adhesive tape achieves excellent flame retardancy and cutting properties, maintaining high adhesive strength even with a low amount of flame retardant, making it suitable for construction applications.
Smart Images

Figure 0007666277000001 
Figure 0007666277000002 
Figure 0007666277000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive tape, and more particularly to an adhesive tape having excellent flame retardancy.
[0002] Conventionally, adhesive tapes have come to be used for various purposes, and in particular, adhesive tapes used for aircraft, automobiles, and construction are required to have improved flame retardancy due to the recent trend of placing more importance on safety. In particular, adhesive tapes used for construction are required to have excellent hand tearability, adhesive properties, and also excellent flame retardancy.
[0003] Methods for imparting flame retardancy to adhesive tapes include incorporating a flame retardant into the base material of the adhesive tape, and incorporating a flame retardant into the adhesive layer. However, in order to maintain the strength of the base material, the method of adding a flame retardant to the adhesive layer rather than incorporating the flame retardant into the base material is used. However, when a flame retardant is contained in the adhesive layer, in order to provide the adhesive tape with sufficient flame retardancy, it is necessary to increase the ratio of the flame retardant to the adhesive in the adhesive layer. Increasing the ratio of the flame retardant tends to reduce the adhesive properties of the adhesive layer, and therefore an adhesive tape having high flame retardancy even if it contains a small amount of flame retardant or no flame retardant at all has been desired. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-179329 A Summary of the Invention [Problem to be solved by the invention]
[0005] The above-mentioned Patent Document 1 discloses an adhesive composition containing a small amount of a phosphate-based flame retardant in the adhesive layer, but the flame retardancy is not sufficient, and even higher flame retardancy is required.
[0006] Under these circumstances, an object of the present invention is to provide an adhesive tape having high flame retardancy even if the adhesive layer does not contain a flame retardant or contains only a small amount of flame retardant. [Means for solving the problem]
[0007] However, the present inventors have conducted extensive research in light of these circumstances and have discovered that by using a substrate comprising a flat yarn cloth, having an adhesive layer on at least one surface of the substrate, the adhesive layer containing an acrylic resin, an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent, and having a gel fraction of the adhesive layer of 50 to 80 mass %, an adhesive tape with excellent flame retardancy and hand tearability can be obtained, thereby completing the present invention.
[0008] That is, the present invention has the following aspects. [1] An adhesive tape having an adhesive layer on at least one surface of a substrate, the substrate comprising a flat yarn cloth, the adhesive layer comprising an acrylic resin, an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent, and the adhesive layer having a gel fraction of 50 to 80 mass%. [2] The adhesive tape according to [1], wherein the acrylic resin contains a carboxyl group-containing monomer unit as a monomer unit thereof. [3] The pressure-sensitive adhesive tape according to [1] or [2], wherein the acrylic resin contains, as a monomer unit thereof, a terminal carboxyl group-containing monomer unit represented by the following general formula (1): [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more. [4] The pressure-sensitive adhesive tape according to any one of [1] to [3], wherein the acrylic resin contains a hydroxyl group-containing monomer unit as a monomer unit thereof. [5] The pressure-sensitive adhesive tape according to any one of [1] to [4], wherein the pressure-sensitive adhesive layer contains less than 10 parts by mass of a flame retardant per 100 parts by mass of an acrylic resin. [6] The pressure-sensitive adhesive tape according to any one of [1] to [5], wherein the pressure-sensitive adhesive layer contains a tackifier. [7] An adhesive tape according to any one of [1] to [6], which has a burning length of 100 mm or less in an ignition test according to EN13501-1, the European fire safety standard for building materials. Effect of the Invention
[0009] The present invention provides an adhesive tape having excellent flame retardancy and hand tearability, which has an adhesive layer containing an acrylic resin, an isocyanate crosslinking agent and an epoxy crosslinking agent as crosslinking agents on at least one side of a substrate containing flat yarn cloth, and has a gel fraction of the flame retardant layer of 50 to 80% by mass. Therefore, the tape is particularly easy to use and can be suitably used as an adhesive tape for construction, which requires high flame retardancy.
[0010] In the present invention, when the acrylic resin contains a carboxyl group-containing monomer as a monomer unit, it is possible to obtain a pressure-sensitive adhesive tape having excellent adhesive properties.
[0011] In the present invention, when the acrylic resin has a terminal carboxyl group-containing monomer represented by the following formula as a monomer unit, a pressure-sensitive adhesive tape having higher flame retardancy can be obtained. [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.
[0012] In the present invention, when the acrylic resin contains a hydroxyl group-containing monomer as a monomer unit, a pressure-sensitive adhesive tape having superior adhesive properties can be obtained.
[0013] In the present invention, when the pressure-sensitive adhesive layer contains less than 10 parts by mass of a flame retardant per 100 parts by mass of an acrylic resin, a pressure-sensitive adhesive tape having excellent adhesive properties can be obtained.
[0014] Furthermore, in the present invention, by including a tackifier in the adhesive layer, an adhesive tape with even better adhesive properties can be obtained. Usually, the inclusion of a tackifier reduces flame retardancy, but the adhesive tape of the present invention is able to retain high flame retardancy.
[0015] Among the adhesive tapes according to the present invention, those having a burning length of 100 mm or less in the ignition test of the European building material fire safety standard EN13501-1 have excellent flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. The acrylic resin is a resin obtained by polymerizing a copolymerization component containing at least one (meth)acrylate monomer. In the present invention, when expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "greater than X is preferable" or "less than Y is preferable."
[0017] An adhesive tape according to one embodiment of the present invention (hereinafter sometimes referred to as "the present adhesive tape") has an adhesive layer on at least one surface of a substrate, the substrate including a flat yarn cloth, the adhesive layer including an acrylic resin, an isocyanate crosslinking agent, and an epoxy crosslinking agent, and the gel fraction of the adhesive layer is 50 to 80 mass %.
[0018] In the present invention, in order to generally impart flame retardancy to an adhesive tape, a flame retardant is added to the substrate or the adhesive layer, but when a flame retardant is added to the substrate, there is a concern that the strength of the substrate is reduced, while when a flame retardant is added to the adhesive layer, there is a concern that the adhesive properties are reduced. In order to exhibit high flame retardant performance even when neither the substrate nor the adhesive layer contains a flame retardant, or the amount of the flame retardant is less than 10 parts by mass relative to 100 parts by mass of the resin component of the adhesive layer, a substrate containing flat yarn cloth is used as the substrate, an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent are contained as crosslinking agents in the adhesive layer, and the gel fraction of the adhesive layer is set to 50 to 80% by mass, thereby making it possible to obtain an adhesive tape with excellent flame retardancy.
[0019] The reason is unclear, but the flat yarn cloth is made by weaving yarns stretched in one direction, and when an ignition source approaches and the temperature rises, it shrinks, and as the ignition source moves away, it becomes difficult for the cloth to catch fire. Even if a fire does catch fire, the adhesive layer contains both an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent, which suppresses the decomposition of the adhesive and makes it difficult for the combustion to continue. Furthermore, if the crosslinking of the adhesive layer progresses sufficiently and the gel fraction is 50% or more by mass, the adhesive layer suppresses the generation of decomposition gas due to heat, making it difficult for the combustion to continue. However, if the gel fraction exceeds 80% by mass, the adhesive layer becomes too hard, which is thought to prevent the shrinkage of the flat yarn cloth and reduce the flame retardancy.
[0020] <<Adhesive layer>> The adhesive layer used in this embodiment is formed from an adhesive obtained by crosslinking an adhesive composition containing an acrylic resin, an isocyanate-based crosslinking agent, and an epoxy-based crosslinking agent. The acrylic resin has a structural unit derived from a specific monomer, i.e., a specific monomer unit. The acrylic resin will be described below.
[0021] <Acrylic resin (A)> The acrylic resin (A) has an acrylic monomer unit, and preferably has a carboxyl group-containing monomer (a1) unit, more preferably a (meth)acrylic acid monomer (a1-1) unit among the carboxyl group-containing monomer (a1) units, and more preferably has a terminal carboxyl group-containing monomer (a1-2) unit having a specific structure.Furthermore, it preferably has a hydroxyl group-containing monomer (a2), particularly a monomer (a3), and further has monomers (a4) to (a5) units as necessary. Each monomer unit will be described below.
[0022] [Monomer (a1) unit] Examples of monomers of the carboxyl group-containing monomer (a1) unit include (meth)acrylic acid, acrylic acid dimer, crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamide N-glycolic acid, cinnamic acid, and terminal carboxyl group-containing monomers having a specific structure described below, etc. Among these, the carboxyl group-containing monomer (a1) is preferably a (meth)acrylic acid monomer (a1-1) or a terminal carboxyl group-containing monomer having a specific structure (a1-2).
[0023] [Monomer (a1-1) unit] The content of the (meth)acrylic acid monomer (a1-1) unit is usually 0.1 to 5 mass%, particularly 0.5 to 4.5 mass%, and more preferably 1 to 4 mass% of the entire acrylic resin (A). If the content is too low, the adhesive properties tend to decrease, whereas if it is too high, the viscosity of the coating liquid tends to increase, and the coatability tends to deteriorate.
[0024] [Monomer (a1-2) unit] The terminal carboxyl group-containing monomer (a1-2) unit having a specific structure refers to a terminal carboxyl group-containing monomer unit represented by the following general formula (1).
[0025] [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.
[0026] Above R 1 is preferably hydrogen, R 2 The hydrocarbon is usually preferably an alkylene, such as a methylene group, having 1 to 10 carbon atoms, more preferably 1 to 5, and particularly preferably 1 to 2 carbon atoms, phenyl, phenylene, or even ethylene, and the above n is preferably 1 to 10, more preferably 1 to 5, particularly preferably 1 to 3, and particularly preferably 1 to 2, and may be a combination of these.
[0027] The content of the monomer (a1-2) unit in the acrylic resin (A) is usually 1 to 20 mass%, particularly 1.5 to 15 mass%, and further preferably 2 to 8.5 mass%. If the content is too low or high, the adhesive properties tend to decrease.
[0028] The acrylic resin (A) having the above monomer (a1-2) units can be obtained by polymerization using a monomer of the following chemical formula (2) as a copolymerizable monomer. [Formula] CH2=CR 1 -CO-O-(R 2 -COO-)nH (2) (where R 1 is hydrogen or a methyl group, R 2represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.
[0029] The content ratio of the monomer (a1-2) unit to the monomer (a1-1) unit is preferably, in mass ratio, usually 10 to 400 parts by mass, particularly 20 to 200 parts by mass, further 25 to 100 parts by mass, and particularly 30 to 75 parts by mass of the monomer (a1-1) unit per 100 parts by mass of the monomer (a1-2) unit. If the amount of the monomer (a1-1) unit is too small, the holding power tends to decrease, whereas if the amount is too large, the viscosity of the coating liquid increases, tending to deteriorate the coatability.
[0030] [Monomer (a2) unit] Examples of copolymerizable monomers for forming the hydroxyl group-containing monomer (a2) units include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl-2-hydroxyethyl (meth)acrylate.
[0031] Among these, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with crosslinking agents, and in particular, hydroxyalkyl (meth)acrylates, 2-hydroxyethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred.
[0032] The hydroxyl group-containing monomer (a2) unit is useful because it becomes a crosslinking point with the isocyanate-based crosslinking agent (b2). The hydroxyl group-containing monomer (a2) unit is usually 0.01 to 5 mass%, particularly 0.05 to 3 mass%, and more preferably 0.05 to 2 mass% of the entire acrylic resin (A). If the monomer (a2) unit is too small, the holding power tends to decrease, and if it is too large, the adhesive properties tend to decrease.
[0033] [Monomer (a3) unit] The acrylic resin (A) used in this embodiment desirably further contains a (meth)acrylate monomer (a3) unit having an alkyl group with 4 to 24 carbon atoms. The copolymerizable monomer for forming the (meth)acrylate monomer (a3) unit having an alkyl group with 4 to 24 carbon atoms may be a (meth)acrylate monomer having any alkyl group with 4 to 24 carbon atoms, and among these, it is preferable to contain a (meth)acrylate monomer (a3-1) having an alkyl group with 4 to 7 carbon atoms and a (meth)acrylate monomer (a3-2) having an alkyl group with 8 to 24 carbon atoms.
[0034] Examples of the (meth)acrylate monomer (a3-1) having an alkyl group having 4 to 7 carbon atoms include n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, etc. Among these, n-butyl (meth)acrylate is preferred because it is easily available and economical.
[0035] Examples of the (meth)acrylate monomer (a3-2) having an alkyl group having 8 to 24 carbon atoms include 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, isotridecyl (meth)acrylate, myristyl (meth)acrylate, isomyristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, etc. Among them, (meth)acrylates having an alkyl group having 8 to 12 carbon atoms are preferred in terms of low polarity and low glass transition temperature, and 2-ethylhexyl (meth)acrylate is particularly preferred.
[0036] The content of the monomer (a3) unit is usually 55 to 97 mass%, particularly 70 to 95 mass%, and further preferably 80 to 93 mass% of the entire acrylic resin (A). If the content is too low, the adhesive properties tend to decrease, whereas if the content is too high, the adhesive properties and holding power tend to decrease.
[0037] The ratio of the monomer (a3-1) unit to the monomer (a3-2) unit is usually (a3-1) / (a3-2)=1 / 99 to 85 / 15, preferably 2 / 98 to 75 / 25, more preferably 3 / 97 to 70 / 30, even more preferably 5 / 95 to 60 / 40, and even more preferably 5 / 95 to 45 / 55 by mass. If the ratio of the monomer (a3-1) unit is too small, the holding power tends to decrease, whereas if it is too large, the adhesive properties tend to decrease.
[0038] [Monomer (a4) unit] The acrylic resin (A) used in this embodiment preferably further contains (meth)acrylate monomer (a4-1) units having an alkyl group with 1 to 3 carbon atoms, cyclic structure-containing monomer (a4-2) units, or vinyl ester monomer (a4-3) units having 3 to 10 carbon atoms. The collective term for the above (a4-1) to (a4-3) is monomer (a4).
[0039] Examples of copolymerizable monomers for forming the (meth)acrylate monomer (a4-1) units having an alkyl group having 1 to 3 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, etc. Among these, methyl (meth)acrylate and ethyl (meth)acrylate are preferred.
[0040] The copolymerizable monomer for forming the cyclic structure-containing monomer (a4-2) unit is usually an acrylic monomer having a substituent containing a cyclic structure, and examples thereof include heterocycle-containing (meth)acrylates having a heterocycle such as a morpholine ring, a piperidine ring, a pyrrolidine ring, or a piperazine ring, such as N-(meth)acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, vinylpyrrolidone, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine, phenyl(meth)acrylate, phenoxyethyl(meth)acrylate, and phenyldiethylene glycol (meth)acrylate. ) acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, nonylphenol polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, isobornyl (meth)acrylate, biphenyloxyethyl (meth)acrylate, and others, such as styrene and α-methylstyrene. Among them, heterocycle-containing (meth)acrylates having a morpholine ring are preferred because of their good balance of various physical properties, and N-(meth)acryloylmorpholine is particularly preferred because of its ease of availability and safety.
[0041] Examples of copolymerizable monomers for forming the vinyl ester monomer (a4-3) units having 3 to 10 carbon atoms include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, etc. Among these, vinyl acetate is preferred because of its easy availability.
[0042] The content of the monomer (a4) unit is usually 11% by mass or less, preferably 10% by mass or less, and particularly preferably 8% by mass or less, based on the total amount of the acrylic resin (A). If the content of the (a4) component is too high, the adhesive properties to the adherend tend to decrease. The lower limit of the content of the (a4) component in the copolymerization component (a) is 0% by mass, but is usually 1% by mass.
[0043] [Monomer (a5) unit] In this embodiment, other copolymerizable monomer (a5) units may be contained as necessary. Examples of the copolymerizable monomer for forming the other copolymerizable monomer (a5) units include functional group-containing monomers such as acetoacetyl group-containing monomers, isocyanate group-containing monomers, glycidyl group-containing monomers, amino group-containing monomers, and amide group-containing monomers, as well as other monomers.
[0044] Examples of the acetoacetyl group-containing monomer include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.
[0045] Examples of the isocyanate group-containing monomer include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and alkylene oxide adducts thereof.
[0046] Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and allyl glycidyl (meth)acrylate.
[0047] Examples of the amino group-containing monomer include monomers having an ethylenically unsaturated double bond and an amino group (unsubstituted or substituted amino group), such as mono-substituted amino group-containing (meth)acrylic acid esters of aminoalkyl (meth)acrylates such as aminomethyl (meth)acrylate, aminoethyl (meth)acrylate, aminopropyl (meth)acrylate, and aminoisopropyl (meth)acrylate, and (meth)acrylic acid esters of N-alkylaminoalkyl such as N-(t-butyl)aminoethyl (meth)acrylate; (meth)acrylic acid esters of N,N-dialkylaminoalkyl such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate. disubstituted amino group-containing (meth)acrylic acid esters such as N,N-dimethylaminopropyl(meth)acrylamide; dialkylaminoalkyl(meth)acrylamides such as N,N-dimethylaminopropyl(meth)acrylamide, and quaternized salts of these amino group-containing monomers; amino group-containing styrenes such as p-aminostyrene; styrenes having a dialkylamino group such as 3-(dimethylamino)styrene and dimethylaminomethylstyrene; dialkylaminoalkyl vinyl ethers such as N,N-dimethylaminoethyl vinyl ether and N,N-diethylaminoethyl vinyl ether; allylamine, 4-diisopropylamino-1-butene, trans-2-butene-1,4-diamine, 2-vinyl-4,6-diamino-1,3,5-triazine, and the like.
[0048] The amide group-containing monomer includes a monomer having an ethylenically unsaturated double bond and an amide group (a group having an amide bond), such as (meth)acrylamide; N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, N-isobutyl(meth)acrylamide, Ns-butyl(meth)acrylamide, Nt-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, da N-alkyl(meth)acrylamides such as acetone(meth)acrylamide, N,N'-methylenebis(meth)acrylamide, and N-(1,1-dimethyl-3-oxobutyl)(meth)acrylamide; N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, N,N-diisobutyl(meth)acrylamide, and N,N-di(s-butyl)(meth)acrylamide; amide, N,N-dialkyl (meth)acrylamides such as N,N-di(t-butyl) (meth)acrylamide, N,N-dipentyl (meth)acrylamide, N,N-dihexyl (meth)acrylamide, N,N-diheptyl (meth)acrylamide, N,N-dioctyl (meth)acrylamide, N,N-diallyl (meth)acrylamide, and N,N-ethylmethylacrylamide; dialkylaminoalkyl (meth)acrylamides such as N,N-dimethylaminopropyl (meth)acrylamide; N-vinylacetamide, N-vinyl phosphatase, and the like. Examples of such amide group-containing monomers include substituted amide group-containing monomers such as N-methylol (meth)acrylamide, (meth)acrylamide ethyl ethylene urea, and (meth)acrylamide-t-butylsulfonic acid; hydroxy group-containing (meth)acrylamides such as N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and N-methylolpropane (meth)acrylamide; alkoxy group-containing (meth)acrylamides such as N-methoxymethyl (meth)acrylamide and N-(n-butoxymethyl) (meth)acrylamide; and quaternized salts of these amide group-containing monomers.
[0049] Examples of the other monomers include monomers containing an alkoxy group or an oxyalkylene group, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and polypropylene glycol mono(meth)acrylate; acrylonitrile, methacrylonitrile, vinyl stearate, vinyl chloride, vinylidene chloride, alkyl vinyl ether, vinyl toluene, dialkyl itaconate, dialkyl fumarate, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethylallyl vinyl ketone.
[0050] The other copolymerizable monomers (a5) may be contained to such an extent that the effects of the present invention are not adversely affected, for example, 10% by mass or less, in order to adjust the physical properties according to the application. The lower limit is usually 0% by mass.
[0051] Thus, the acrylic resin (A) is obtained by appropriately polymerizing the above monomers (a1) to (a5). That is, the acrylic resin (A) having the above monomer units (a1) to (a5) is obtained. The monomer units (a1) to (a5) may be each used alone or in combination of two or more kinds.
[0052] In the above polymerization, it is preferable to carry out the production by solution polymerization, since the acrylic resin (A) can be safely and stably produced with any monomer composition. It is particularly preferable to carry out the polymerization in an organic solvent, and the acrylic resin (A) polymerized in an organic solvent becomes an organic solvent-based acrylic resin.
[0053] Such solution polymerization may be carried out according to a conventional method, for example, by mixing or dropping copolymerization components such as the monomers (a1) to (a5) and a polymerization initiator into an organic solvent, and polymerizing the mixture under reflux or at 50 to 98° C. for 0.1 to 20 hours.
[0054] Specific examples of such polymerization initiators include azo-based polymerization initiators such as azobisisobutyronitrile and azobisdimethylvaleronitrile, which are normal radical polymerization initiators, and peroxide-based polymerization initiators such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide. These may be used alone or in combination of two or more. The amount of the polymerization initiator used is usually 0.001 to 5 parts by mass per 100 parts by mass of the copolymerization component (a).
[0055] The mass average molecular weight of the acrylic resin (A) thus obtained is usually 100,000 to 5,000,000, preferably 300,000 to 1,500,000, and particularly preferably 400,000 to 900,000. If the mass average molecular weight is too small, the durability tends to decrease, and if it is too large, the adhesive strength tends to decrease.
[0056] The dispersity (mass average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, particularly preferably 15 or less, further preferably 10 or less, and especially preferably 7 or less. If the dispersity is too high, the durability of the pressure-sensitive adhesive layer tends to decrease and foaming and the like tends to occur easily. The lower limit of the dispersity is usually 1.1 from the viewpoint of production limitations.
[0057] The mass average molecular weight of the acrylic resin (A) is a mass average molecular weight calculated based on the molecular weight of standard polystyrene. The mass average molecular weight was measured by a high performance liquid chromatograph (Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)") using a Shodex GPC KF-806L column (molecular weight exclusion limit: 2×10 7 , Separation range: 100~2×10 7 The number average molecular weight is measured by using three columns in series (10000 / column, theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm), and the same method can be used for measuring the number average molecular weight.
[0058] The glass transition temperature (Tg) of the acrylic resin (A) is preferably from -80 to 10°C, particularly from -70 to -10°C, and further preferably from -65 to -20°C. If the glass transition temperature is too high, the tack tends to be insufficient, whereas if the glass transition temperature is too low, the heat resistance tends to decrease.
[0059] The glass transition temperature (Tg) is a value calculated by applying the glass transition temperature and mass fraction of each of the monomers constituting the acrylic resin (A) as a homopolymer to the following Fox's formula.
[0060]
number
[0061] Here, the glass transition temperature when the monomer constituting the acrylic resin (A) is made into a homopolymer is usually a value measured by a differential scanning calorimeter (DSC) according to a method in accordance with JIS K7121-1987 or JIS K6240, or a value listed in a catalog.
[0062] The acrylic resin (A) is usually adjusted in viscosity with a solvent or the like, and is used for coating as an acrylic resin (A) solution. The viscosity of the acrylic resin (A) solution is preferably 500 to 20,000 mPa·s / 25°C from the viewpoint of ease of handling, particularly preferably 1,000 to 18,000 mPa·s / 25°C, and more preferably 2,000 to 15,000 mPa·s / 25°C. If the viscosity is too high, the fluidity tends to decrease and handling becomes difficult, and if the viscosity is too low, coating of the adhesive tends to become difficult. The solution concentration during coating is usually 10 to 70% by mass.
[0063] The solvent is not particularly limited as long as it dissolves the acrylic resin (A), but an organic solvent is preferred, and for example, ester solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol solvents such as methanol, ethanol, and propyl alcohol can be used. Among these, ethyl acetate and methyl ethyl ketone, especially ethyl acetate, are preferably used in terms of solubility, drying property, and price. These solvents may be used alone or in combination of two or more.
[0064] The viscosity of the acrylic resin (A) solution is measured by adjusting the temperature of the resin solution to 25° C. using a rotational viscometer method using a B-type viscometer.
[0065] <Crosslinking agent (B)> The pressure-sensitive adhesive composition contains a crosslinking agent (B) in addition to the acrylic resin (A).
[0066] The crosslinking agent (B) reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure, and is particularly used in combination with an epoxy crosslinking agent (b1) and an isocyanate crosslinking agent (b2). By using them in combination, the effect of improving flame retardancy is enhanced. The reason for this is unclear, but it is believed that by using the epoxy-based crosslinking agent (b1) in combination with the isocyanate-based crosslinking agent (b2), it is possible to form an adhesive layer with a uniform crosslink density, and it is possible to improve the flame retardant performance with the addition of a small amount of flame retardant or no flame retardant at all. With only the epoxy-based crosslinking agent (b1), the crosslinked structure is hydrolyzed by the moisture generated during combustion, reducing the crosslink density, which is thought to make it easier for combustion to continue, and with only the isocyanate-based crosslinking agent (b2), the crosslink density becomes non-uniform, resulting in insufficient flame retardant performance.
[0067] Examples of the epoxy crosslinking agent (b1) include aliphatic epoxy crosslinking agents such as ethylene glycol diglycidyl ether, trimethylolpropane diglycidyl ether, and diglycidylamine; alicyclic epoxy crosslinking agents such as 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, and N,N,N',N'-tetraglycidyl-m-xylylenediamine; aromatic epoxy crosslinking agents such as diglycidylaniline; heterocyclic epoxy crosslinking agents such as 1,3,5-tris-(2,3-epoxybutyl)-isocyanurate, 1,3,5-tris-(3,4-epoxybutyl)-isocyanurate, and 1,3,5-tris-(4,5-epoxypentyl)-isocyanurate, among which alicyclic epoxy crosslinking agents are preferred. These can be used alone or in combination of two or more.
[0068] The isocyanate-based crosslinking agent (b2) contains at least two isocyanate groups, and examples thereof include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, and alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, as well as their biuret and isocyanurate forms, and further adducts which are reaction products with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. In particular, the adduct of tolylene diisocyanate and trimethylolpropane is preferred. These can be used alone or in combination of two or more.
[0069] The content of the epoxy crosslinking agent (b1) is usually 0.02 to 0.5 parts by mass, particularly 0.03 to 0.45 parts by mass, further 0.035 to 0.4 parts by mass, and particularly preferably 0.04 to 0.35 parts by mass, relative to 100 parts by mass of the acrylic resin (A). When the content is within the above range, the flame retardancy tends to be excellent.
[0070] The content of the isocyanate-based crosslinking agent (b2) is usually 0.4 to 9 parts by mass, particularly 0.5 to 8 parts by mass, further 0.6 to 7 parts by mass, and particularly preferably 0.7 to 6 parts by mass, based on 100 parts by mass of the acrylic resin (A). When the content is within the above range, the flame retardancy tends to be excellent.
[0071] The content ratio of the epoxy crosslinking agent (b1) to the isocyanate crosslinking agent (b2) is, in terms of mass ratio (b1 / b2), usually 0.001 to 1, particularly 0.005 to 0.5, and further preferably 0.01 to 0.1.
[0072] The above crosslinking agent can be used after being diluted with a solvent or the like, but the above content and content ratio indicate the actual content and content ratio of the crosslinking agent excluding the solvent and the like.
[0073] In the present invention, the crosslinking agents of the above-mentioned (b1) and (b2) components are used in combination, but other crosslinking agents may also be used in combination within a range that does not impair the effects of the present invention. Examples of other crosslinking agents include aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, and metal chelate-based crosslinking agents. These may be used alone or in combination of two or more types, but the effects of the present invention are not achieved with a combination of crosslinking agents that does not include the (b1) or (b2) component. The content of the other crosslinking agent is preferably 5 parts by mass or less, particularly preferably 1 part by mass or less, and more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the acrylic resin (A). The lower limit is usually 0 parts by mass.
[0074] Examples of the aziridine-based crosslinking agent include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), trimethylolpropane tri-β-aziridinylpropionate, tetramethylolmethane tri-β-aziridinylpropionate, toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, bisisophthaloyl-1-(2-methylaziridine), tris-1-(2-methylaziridine)phosphine, trimethylolpropane tri-β-(2-methylaziridine)propionate, and the like.
[0075] Examples of the melamine-based crosslinking agent include melamine; methylolmelamine derivatives such as amino group-containing methylolmelamine, imino group-containing methylolmelamine, and hexamethylolmelamine obtained by condensing melamine with formaldehyde; and alkylated methylolmelamines such as partially or completely alkylated methylolmelamine and imino group-containing partially or completely alkylated methylolmelamine obtained by reacting a methylolmelamine derivative with a lower alcohol such as methyl alcohol or butyl alcohol to partially or completely etherify the methylolmelamine derivative.
[0076] Examples of the aldehyde crosslinking agent include aldehyde compounds that liberate aldehyde in an aqueous solution, such as formaldehyde, acetaldehyde, propionaldehyde, butylaldehyde, glyoxal, glutaraldehyde, dialdehyde starch, hexamethylenetetramine, 1,4-dioxane-2,3-diol, 1,3-bis(hydroxymethyl)-2-imidazolidine, dimethylol urea, N-methylol acrylamide, urea formalin resin, and melamine formalin resin, and aromatic aldehyde compounds, such as benzaldehyde, 2-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, and m-hydroxybenzaldehyde.
[0077] Examples of the amine-based crosslinking agent include 4,4'-methylene-bis(2-chloroaniline) (hereinafter abbreviated as "MOCA"), modified MOCA, and diethyltoluenediamine.
[0078] The above-mentioned metal chelate crosslinking agent can be, for example, chelate compounds whose metal atom is aluminum, zirconium, titanium, zinc, iron, tin, etc., and aluminum chelate compounds are preferred from the viewpoint of performance.As the aluminum chelate compounds, for example, diisopropoxyaluminum monooleyl acetoacetate, monoisopropoxyaluminum bisoleyl acetoacetate, monoisopropoxyaluminum monooleate monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, etc. can be mentioned.
[0079] <Flame retardant (C)> The pressure-sensitive adhesive tape can contain a flame retardant (C) within a range that does not impair the effects of the present invention. From the viewpoint of adhesive properties, the content of the flame retardant (C) is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably 1 part by mass or less, per 100 parts by mass of the acrylic resin (A). In addition, the pressure-sensitive adhesive tape can have flame retardancy even without containing the flame retardant (C).
[0080] The flame retardant (C) may be any known flame retardant generally used as a flame retardant for adhesives, such as phosphorus-based flame retardants, metal hydroxyl-based flame retardants, metal phosphinate-based flame retardants, halogen-based flame retardants, a combination of a halogen-based flame retardant and antimony trioxide, nitrogen-containing compounds such as melamine cyanurate and triazine compounds, etc. These may be used alone or in combination of two or more.
[0081] Examples of phosphorus-based flame retardants include non-halogen phosphate esters such as trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, 2-naphthyl diphenyl phosphate, and cresyl di-2,6-xylenyl phosphate; aromatic condensed phosphate esters such as "CR-733S," "CR-741," and "PX-200" manufactured by Daihachi Chemical Industry Co., Ltd.; non-halogen condensed phosphate esters such as "DAIGUARD-580," "DAIGUARD-610," and "DAIGUARD-880" manufactured by Daihachi Chemical Industry Co., Ltd.; amine phosphate salts such as melamine polyphosphate; and ammonium polyphosphate that is not coated with a resin or is coated with melamine or the like.
[0082] Among these, polyphosphates are preferred because they contain no halogen but have a high phosphorus concentration, making them highly flame retardant, and because even a small amount can be added to impart flame retardancy without reducing the adhesive properties. Of these, ammonium polyphosphate is preferred, and ammonium polyphosphate coated with melamine or the like is particularly preferred because it inhibits hydrolysis and has excellent resistance to moist heat.
[0083] Examples of metal hydroxyl group-based flame retardants include magnesium hydroxide and aluminum hydroxide.
[0084] Examples of the metal phosphinate flame retardant include "Exolit OP1230" and "Exolit OP930" manufactured by Clariant.
[0085] Examples of halogen-based flame retardants include bromine-based flame retardants such as tetrabromobisphenol A, hexabromocyclodecane, dibromodiphenyl oxide, tetrabromobisphenol A polycarbonate oligomer, brominated polystyrene, ethylene bistetrabromophthalimide, etc.; chlorine-based flame retardants such as chlorinated paraffin, perchlorocyclopentadecane, etc.; halogen-containing phosphate esters such as tris(tribromoneopentyl)phosphate, tris(chloropropyl)phosphate, etc.; and halogen-containing condensed phosphate esters such as "CR-504L", "CR-570", and "DAIGUARD-540" manufactured by Daihachi Chemical Industry Co., Ltd.
[0086] Among these, since halogen-containing flame retardants may generate toxic halogen gases or corrode metals when incinerated, it is preferable that the flame retardant (C) is a halogen-free flame retardant.
[0087] In addition, for example, in the case of a compound product (composite, composite material), it is said that a synergistic effect can be obtained by using a flame retardant (C) in combination with another flame retardant having a different mechanism of action rather than using the flame retardant alone. However, in the present invention, it is preferable to use the flame retardant alone from the viewpoint of not decreasing the adhesive strength or compatibility with the adhesive. In particular, the phosphorus-based flame retardants exemplified above are preferred, and ammonium polyphosphate coated with melamine or the like is particularly preferred, as it provides excellent flame retardancy with little deterioration in adhesive properties, and also inhibits hydrolysis and has excellent resistance to moist heat.
[0088] <Tackifier (D)> The tackifier (D) is not an essential component, but is used to further exert the good physical properties of the acrylic resin (A), and is preferably contained in the adhesive composition. Examples of the tackifier (D) include resins that are compatible with the acrylic resin (A), such as rosin-based resins, terpene-based resins, xylene-based resins, phenol-based resins, coumarone-based resins, and petroleum-based resins. These tackifiers (D) can be used alone or in combination of two or more. Among them, rosin-based resins, terpene-based resins, and petroleum-based resins are preferred.
[0089] Examples of the rosin resin include a rosin ester resin obtained by hydrogenating, disproportionating, dimerizing, and adding an acid to a raw rosin, and then esterifying the resultant with glycerin or pentaerythritol, and a rosin phenol resin obtained by adding phenol. Any of the rosin resins can be used to further exhibit the good physical properties of the acrylic resin (A). Among them, preferred are a disproportionated rosin ester obtained by disproportionating the raw rosin and esterifying it with glycerin or pentaerythritol, which has a softening point in the range of 70 to 130°C, a polymerized rosin ester obtained by dimerizing the raw rosin and esterifying it with pentaerythritol, which has a softening point in the range of 110 to 170°C, and a rosin phenol obtained by adding phenol to the raw rosin, which has a softening point in the range of 120 to 160°C.
[0090] The above terpene resin has the molecular formula (C5H8) n The tackifier (D) used in this embodiment is a resin obtained by homopolymerization or copolymerization of monoterpene (e.g., α-pinene, β-pinene, limonene, etc.) with a Friedel-Crafts catalyst. Specifically, examples of the resin obtained by homopolymerization or copolymerization of monoterpene include α-pinene resin, β-pinene resin, dipentene resin, terpene phenol resin, aromatic modified terpene resin, and hydrogenated terpene resin obtained by hydrogenating these resins. Among these, terpene phenol resins are preferred due to their good compatibility with the acrylic resin (A). Any of the terpene phenol resins will further enhance the good physical properties of the acrylic resin (A). In particular, those having a softening point of 90 to 170°C and a hydroxyl value in the range of 20 to 250 (mgKOH / g) are preferred, and those having a softening point of 100 to 150°C and a hydroxyl value in the range of 50 to 150 (mgKOH / g) are more preferred.
[0091] The petroleum resin is obtained, for example, by polymerization and further hydrogenation of C4-C5 and C9-C11 fraction monomers produced by thermal decomposition of naphtha, etc., and depending on the type of raw material fraction, examples include pure monomer resins, aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, hydrogenated petroleum resins, etc. Any of the petroleum resins can be used to further exhibit the good physical properties of the acrylic resin (A), but among them, those with a softening point in the range of 90 to 130°C are preferred, and it is further preferred to use a copolymerization system of a styrene monomer and an aliphatic monomer.
[0092] The content of the tackifier (D) is usually 1 to 50 parts by mass, particularly 5 to 30 parts by mass, and further preferably 5 to 20 parts by mass, per 100 parts by mass of the acrylic resin (A), and is appropriately blended depending on the required physical properties.
[0093] Furthermore, the adhesive composition may contain, as other components, various additives such as resin components other than the acrylic resin (A), acrylic monomers, polymerization inhibitors, antioxidants, corrosion inhibitors, crosslinking accelerators, radical generators, peroxides, ultraviolet absorbers, plasticizers, pigments, stabilizers, fillers, and radical scavengers, metals, and resin particles, within the scope of the invention. These may be used alone or in combination of two or more. In addition to the above, the adhesive composition may contain a small amount of impurities contained in the manufacturing raw materials of the components of the adhesive composition.
[0094] The content of the other components is preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the acrylic resin (A). The lower limit is usually 0 parts by mass. If the content is too high, the compatibility with the acrylic resin (A) decreases, and the durability tends to decrease. However, for additives (pigments, fillers, metals, resin particles, etc.) that do not exert their effects at the above content, an appropriate amount may be added within a range that exerts the effect of the additive while not inhibiting the effects of the present invention.
[0095] As described above, the pressure-sensitive adhesive composition contains the acrylic resin (A), the crosslinking agent (B), and, if necessary, the flame retardant (C), as well as the tackifier (D) and other components. The method for preparing the pressure-sensitive adhesive composition is not particularly limited, but in addition to the commonly known mechanical kneading dispersion method, known methods such as a solvent dispersion method and an ultrasonic dispersion method can be used as necessary.
[0096] By mixing the above components, a pressure-sensitive adhesive composition can be obtained. In addition, by crosslinking this pressure-sensitive adhesive composition, a pressure-sensitive adhesive can be obtained. This pressure-sensitive adhesive can be applied to various substrates to be used as a pressure-sensitive adhesive tape, and is particularly suitable for use as a pressure-sensitive adhesive layer of a flame-retardant pressure-sensitive adhesive tape.
[0097] <<Adhesive tape>> The adhesive tape contains an adhesive obtained by crosslinking the adhesive composition as an adhesive layer. Specifically, the adhesive composition is dissolved in a solvent such as ethyl acetate to prepare an adhesive composition solution for coating so that the solid content concentration is 10 to 70 mass%, and the solution is applied to a substrate and dried to produce an adhesive tape. The adhesive composition prepared as above is an organic solvent-based adhesive composition, and when it is crosslinked, it becomes an organic solvent-based adhesive.
[0098] Such an adhesive tape may be produced by a known method for producing an adhesive tape, for example, by coating one side of a substrate with an adhesive and drying it, and then overlaying a release liner on the surface of the formed adhesive layer, or by coating one side of a release liner with an adhesive and drying it, and then overlaying a substrate on the surface of the formed adhesive layer. Among these, the method of coating one side of a release liner with an adhesive and drying it, and then overlaying a substrate on the surface of the formed adhesive layer is preferred from the viewpoint of handling, etc.
[0099] <Base material> The substrate used in this embodiment contains flat yarn cloth and is preferably hand-cuttable. The surface of the substrate may be appropriately subjected to a known and commonly used surface treatment, such as a physical treatment such as corona discharge treatment or plasma treatment, or a chemical treatment such as undercoat treatment.
[0100] The substrate is not particularly limited as long as it is a conventionally known substrate containing a flat yarn cloth, and examples thereof include a laminated film in which a plastic film is laminated to a flat yarn cloth.
[0101] Flat yarn cloth is a woven fabric made by cutting polyethylene or polypropylene films called flat yarns into strips and stretching them to give them strength, and the intersections of the flat yarns that cross vertically and horizontally of this woven fabric are fixed by heat fusion to prevent misalignment. As the material for the flat yarns, olefin resins such as polyethylene and polypropylene are preferred, polyethylene is more preferred, and high-density polyethylene is particularly preferred.
[0102] Furthermore, the present adhesive tape is preferably provided with hand-tearability, and the flat yarn cloth used in the hand-tearable adhesive tape is preferably one that is easily torn in the width direction, for example, by using flat yarns that are thinner in the longitudinal direction than in the width direction, or by making the number of flat yarns per length in the width direction less than the number in the longitudinal direction. Such flat yarn cloth is difficult to tear in the longitudinal direction. Another feature of the flat yarn cloth provided with hand-tearability is that it has high tensile strength in the longitudinal direction.
[0103] Compared with woven substrates such as flat yarn cloth, substrates reinforced with non-woven fibers have very low tensile strength. Therefore, in order to compensate for the tensile strength, it is conceivable to improve the tensile strength by laminating a biaxially oriented polyester film or a biaxially oriented polypropylene film with an adhesive. However, such a structure has problems in that it is difficult to tear in the width direction, and the substrate tends to be heavy because an adhesive is required to bond the warp and weft threads.
[0104] The mass per unit area of this adhesive tape is 300 g / m 2 It is preferable that the mass per unit area of the substrate is 200 g / m or less, and the substrate is also preferably light. 2 It is preferable that the thickness is less than 100 g / m 2 The following is the result. The lower limit of the mass per unit area of the substrate is, for example, 10 g / m 2 is preferred.
[0105] The use of a substrate in which a plastic film is laminated on a flat yarn cloth is preferable in terms of obtaining stable adhesive strength and peelability. In the case of a double-sided adhesive tape, the presence of a plastic film is believed to prevent the adhesive on one side from passing through the substrate and mixing with the adhesive on the other side, and to suppress the transfer of additives of the adhesive layer on one side, such as crosslinking agents, flame retardants, and plasticizers, to the adhesive layer on the other side. In addition, laminating a plastic film on a flat yarn cloth improves hand-cutting properties and linearity of the fracture surface, possibly because the breaking point is smoothly propagated. As the plastic film, a polyethylene film is preferable, and a low-density polyethylene film is more preferable.
[0106] In addition, the substrate in which the plastic film is laminated to the flat yarn cloth is preferably lightweight, and the plastic film is preferably thin. The thickness of the plastic film is preferably 10 to 80 μm. The plastic film may be laminated to only one side of the flat yarn cloth, or may be laminated to both sides. As for the method of laminating the film to the flat yarn cloth, extrusion lamination is preferable because it can reduce weight without using an adhesive.
[0107] The thickness of the substrate containing the flat yarn cloth is preferably 10 to 200 μm, more preferably 50 to 180 μm, and even more preferably 60 to 150 μm. If the thickness is too thin, the hand-tearability is improved but defects such as the inclusion of wrinkles during the production of the adhesive tape tend to increase, whereas if the thickness is too thick, defects during the production of the adhesive tape are reduced but a larger force is required to cut, and the hand-tearability tends to decrease.
[0108] <Release liner> Examples of the release liner include plastic films made of plastics such as polyolefin resins such as polyethylene, polyester resins such as polyethylene terephthalate, vinyl acetate resins, polyimide resins, fluorine resins, and cellophane; paper such as kraft paper and Japanese paper; rubber sheets made of natural rubber, butyl rubber, and the like; foam sheets obtained by foaming polyurethane, polychloroprene rubber, and the like; metal foils such as aluminum foil and copper foil; composites of these, etc. Furthermore, these may be subjected to a surface treatment such as a corona treatment on one or both sides.
[0109] Further, examples of the release liner include paper obtained by laminating a film such as polyethylene onto glassine paper, craft paper, or clay-coated paper; paper coated with a resin such as polyvinyl alcohol or an acrylic acid ester copolymer; and synthetic resin films such as polyester or polypropylene coated with a release agent such as a fluorine-based resin or a silicone-based resin. These can be used alone or in combination of two or more.
[0110] Among these, paper release liners are preferred because they are easily torn by hand, and the basis weight of the base paper is 40 to 120 g / m 2 , preferably 50 to 80 g / m 2 Particularly preferred is a paper release liner having a thickness of 40 to 180 μm, particularly 60 to 140 μm, and further preferably 80 to 120 μm. If the thickness is too thin, wrinkles may occur during winding, making production difficult, while if the thickness is too thick, hand tearability may decrease.
[0111] The coating device used when coating one side of the above-mentioned substrate or release liner with the adhesive may be any commonly used coating device, such as a roll knife coater, die coater, roll coater, bar coater, gravure roll coater, reverse roll coater, dipping, blade coater, etc.
[0112] The thickness of the pressure-sensitive adhesive layer after drying is preferably from 5 to 200 μm, particularly preferably from 10 to 150 μm, and further preferably from 15 to 130 μm. If the thickness is too thick, it tends to be difficult to apply the adhesive, whereas if the thickness is too thin, sufficient adhesive strength tends to be difficult to obtain.
[0113] The drying conditions may be any conditions under which the solvent and residual monomers in the adhesive are dried and removed during drying, and when a crosslinking agent (B) is used, the functional group of the acrylic resin (A) reacts with the crosslinking agent (B) to form a crosslinked structure. For example, drying conditions are preferably 60 to 120°C and about 1 to 5 minutes. After drying, the adhesive layer is sandwiched between sheet-like substrates and aged to further promote the crosslinking reaction.
[0114] The pressure-sensitive adhesive tape may be a single-sided pressure-sensitive adhesive tape or a double-sided pressure-sensitive adhesive tape. The pressure-sensitive adhesive layers of the double-sided pressure-sensitive adhesive tape may be the same pressure-sensitive adhesive layer or may be pressure-sensitive adhesive layers having different compositions.
[0115] In addition, when a release liner is laminated on the adhesive layer of the double-sided adhesive tape, it is preferable to select the release liners laminated on both sides so that their peel strengths are different in order to improve workability. For example, the workability is improved by selecting a release liner that has a smaller peel strength on the side of the double-sided adhesive tape that is first applied than on the side of the double-sided adhesive tape that is next applied.
[0116] The adhesive tape may be in the form of a roll or in the form of sheets, or may be further processed into various shapes. When the adhesive tape is a double-sided adhesive tape in a sheet state, it is preferable that a release liner be provided on the surface of both of the two adhesive layers, and when it is in a roll state, it is preferable that a release liner be provided on the surface of only one of the two adhesive layers.
[0117] Thus, the present adhesive tape is obtained, which has good holding power and does not lose its adhesive properties even when applied to adherends or substrates that would otherwise cause a decrease in adhesive properties. Furthermore, when a substrate having hand-tearability is used as the substrate, the tape can be easily cut by hand at any desired position in the width direction of the tape without using a tape cutter or the like, making the tape particularly useful as an adhesive tape.
[0118] The adhesive strength of the adhesive layer in the above-mentioned adhesive tape is preferably such that the 180° peel strength in accordance with JIS Z0237 against the adherend to be used is 1 to 100 N / 25 mm.
[0119] In particular, when a test plate made of SUS304 stainless steel, which has a relatively high polarity, is used as the adherend, the 180° peel strength is preferably 10 N / 25 mm or more, particularly preferably 20 N / 25 mm or more, and further preferably 30 N / 25 mm or more. The upper limit is usually about 100 N / 25 mm.
[0120] The adhesive strength varies depending on the composition (material) and surface condition (surface roughness) of the adherend, treatment (cleaning) conditions, etc., and is not limited to the above peel strength range.
[0121] The adhesive strength is a value measured in accordance with JIS Z 0237. Specifically, an adhesive tape is cut to a width of 25 mm and a length of 150 mm, and the adhesive layer of the adhesive tape is pressed onto a test plate, and the adhesive tape is peeled off from the test plate at a peel angle of 180° and a speed of 300 mm / min, to measure the peel strength.
[0122] If the test piece is a double-sided adhesive tape, the adhesive side not being tested can be measured by covering it with a polyethylene terephthalate film (Lumirror S10, manufactured by Toray Industries, Inc.) having a nominal thickness of 25 μm as specified in JIS C2318.
[0123] Furthermore, when the holding strength of the adhesive layer in this adhesive tape is measured using the <Method for measuring holding strength> described below, it is particularly preferable that the test piece does not fall off the test plate after 24 hours (1,440 minutes) has elapsed, and even if the test piece falls off within 24 hours, the holding time is preferably 100 minutes or more, more preferably 150 minutes or more, and particularly preferably 500 minutes or more.
[0124] <Method of measuring holding power> The adhesive tape was cut to a width of 25 mm and a length of 75 mm, and the adhesive layer of the tape was pressed against a SUS plate so that the contact area between the tape and the plate was 25 mm wide x 25 mm long. A 1000g weight was then attached to the SUS plate so that the adhesive tape was hanging vertically from the plate, and the time it took for the tape to fall was then measured in an environment of 40°C.
[0125] The gel fraction of the adhesive layer of the present adhesive tape is 50 to 80% by mass. In particular, it is preferably 52 to 80% by mass, particularly 53 to 79% by mass, further 55 to 79% by mass, and especially 60 to 76% by mass, so that an adhesive tape having high flame retardancy can be obtained. In order to make the gel fraction within the above range, the type and content of the epoxy-based crosslinking agent (b1) and the isocyanate-based crosslinking agent (b2) may be adjusted.
[0126] Furthermore, if the gel fraction is too low, the flame retardancy decreases, whereas if it exceeds 80 mass %, the pressure-sensitive adhesive layer becomes too hard, and therefore shrinkage of the substrate does not occur, resulting in a decrease in flame retardancy.
[0127] The gel fraction is an indicator of the degree of crosslinking (degree of curing) and can be measured, for example, by the method described in the Examples below.
[0128] The gel fraction of the pressure-sensitive adhesive can be adjusted to fall within the above range by adjusting the type and amount of the crosslinking agent (B), for example.
[0129] In a flame retardancy test according to ISO11925-2, which is an ignition test standard defined in the European fire safety standard EN13501-1, the present pressure-sensitive adhesive tape preferably has a burning length of 100 mm or less, more preferably 90 mm or less, even more preferably 80 mm or less, even more preferably 70 mm or less, and even more preferably 60 mm or less.
[0130] In addition, the adhesive tape preferably has a large tensile strength, and is required to have the strength necessary to pull the tape without distortion when it is attached to an adherend or to peel it off for position correction. The tensile strength of the adhesive tape is preferably 20N / 25mm or more, more preferably 30N / 25mm or more, and even more preferably 40N / 25mm or more. The upper limit of the tensile strength is usually 250N / 25mm. To obtain an adhesive tape with a large tensile strength, a film having a tensile strength of the substrate equal to or greater than the tensile strength of the desired adhesive tape can be used.
[0131] This pressure-sensitive adhesive tape has excellent flame retardancy, and can therefore be used in a wide range of applications, such as packaging tapes, such as flame-retardant adhesive tapes, flame-retardant adhesive tapes, craft tapes, OPP tapes, and cloth adhesive tapes, cellophane adhesive tapes for light packaging, foam tapes for automobiles, vibration-damping sheets, protective tapes for housing, soundproofing seals, double-sided tapes for fixing carpets, vinyl tapes for electrical insulation, outdoor anticorrosive tapes, tapes for indoor displays, slip prevention tapes, adhesive tapes for airtight waterproofing, adhesive substrates for medical first aid bandages, surgical tapes, adhesive bandages, tapes for electrical and electronic equipment, double-sided tapes for optics, dicing tapes for semiconductors, thermal conductive tapes, heat-resistant tapes, and conductive tapes.
[0132] In particular, it can be suitably used for adhesive tapes for construction. EXAMPLES
[0133] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.
[0134] First, various acrylic resins (A) were prepared as follows. The mass average molecular weight, dispersity, glass transition temperature, and viscosity of the acrylic resin (A) were measured according to the methods described above.
[0135] <Acrylic resin (A)> Prior to the production of the acrylic resin (A), the following were prepared as copolymerization components (a) to be used in the production. Component (a1-1) Acrylic Acid Component (a1-2) A monomer having a terminal carboxyl group represented by the following general formula (2): CH2=CR 1 -CO-O-(R 2 -COO-) n H (2) In the above general formula (2), R 1 is hydrogen, R2 is an ethylene chain, n is 1 to 5 (a2) Component 2-Hydroxyethyl methacrylate (a3-1) Component n-Butyl acrylate (a3-2) Component 2-Ethylhexyl acrylate (a4-1) Component Methyl acrylate
[0136] [Production of acrylic resin (A)] In a reactor equipped with a thermometer, a stirrer, and a reflux condenser, 5 parts of Sipomer H [3.6 parts of a terminal carboxyl group-containing monomer (a1-2) represented by the general formula (2), 1.4 parts of acrylic acid (a1-1)], 0.1 parts of 2-hydroxyethyl methacrylate (a2), 25.8 parts of n-butyl acrylate (a3-1), 63.1 parts of 2-ethylhexyl acrylate (a3-2), 6 parts of methyl acrylate (a4-1), 55 parts of ethyl acetate as a solvent, and 0.15 parts of azobisisobutyronitrile as a polymerization initiator were charged as copolymerization components, and the temperature was raised with stirring. After polymerization for 7 hours at the reflux temperature of the ethyl acetate (mixture), the reaction mixture was diluted with ethyl acetate to obtain an acrylic resin (A) solution with a solid content of 56% and a viscosity of 7000 mPa·s / 25°C. The resulting acrylic resin (A) had a mass average molecular weight of 620,000, a polydispersity of 5.8, and a glass transition temperature of -59°C.
[0137] <Crosslinking agent (B)> The following was prepared as the crosslinking agent (B). Epoxy crosslinking agent (b1): Tetrad C (1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane), manufactured by Mitsubishi Gas Chemical Company, Inc. Isocyanate-based crosslinking agent (b2): Tosoh Corporation, Coronate L-55E (solid content 55%)
[0138] <Tackifier (D)> The following tackifiers were prepared: Disproportionated rosin ester: Arakawa Chemical Industries, Super Ester A-100 (glycerin ester of disproportionated rosin, softening point 95-105°C)
[0139] <Example 1> For 100 parts of the solid content (resin content) of the acrylic resin (A) solution prepared as described above, 0.042 parts of epoxy-based crosslinking agent (b1) (Tetrad C) converted to solid content (resin content), 0.71 parts of isocyanate-based crosslinking agent (b2) (Coronate L-55E) converted to solid content (resin content), and 15 parts of tackifier (D) were mixed, and the solution was adjusted to a solid content concentration of 40% with ethyl acetate and stirred until uniform, thereby obtaining a solution of an adhesive composition.
[0140] <Examples 2 to 4 and Comparative Examples 1 to 9> The same procedure as in Example 1 above was carried out except that the components of the adhesive composition were changed as shown in Table 1 below, to obtain adhesive composition solutions of Examples 2 to 4 and Comparative Examples 1 to 9.
[0141] For the obtained pressure-sensitive adhesive compositions of Examples 1 to 4 and Comparative Examples 1 to 9, pressure-sensitive adhesive tapes were produced as described below and the following evaluations were carried out. The evaluation results are shown in Table 1 below.
[0142] [Preparation of adhesive tape] The solution of the adhesive composition prepared as described above was applied to the release surface of a paper release liner [SS-70-SBX (Shinomura Chemical Industry Co., Ltd.)] using an applicator so that the thickness after drying would be 100 μm, and then dried at 80° C. for 5 minutes, and a substrate (manufactured by Diatex Co., Ltd., thickness 130 μm) made of a low-density polyethylene film laminated on both sides of a high-density polyethylene flat yarn cloth was attached. Then, a heat aging treatment was performed in a dryer at 40° C. for 7 days to prepare an adhesive tape.
[0143] <Gel fraction> A 200-mesh SUS wire mesh large enough to encase the resulting adhesive tape is prepared and its mass is measured (1). The paper release liner is peeled off from the adhesive tape and wrapped in the aforementioned SUS wire mesh, and the mass of the tape together with the wire mesh is measured (2). After immersion in toluene maintained at 23°C for 48 hours, it is thoroughly dried and the mass of the tape together with the wire mesh is measured (3). After immersion, the tape is removed from the wire mesh, the remaining adhesive layer is removed, and the mass of the base material is measured (4). Subtraction is performed as shown in the following formula, and the mass percentage of the adhesive component after immersion compared to before immersion is determined as the gel fraction. [Formula] Gel fraction (mass%) = (mass of tape after immersion including the mass of SUS wire mesh (3) - mass of substrate (4) - mass of SUS wire mesh (1)) / (mass of tape before immersion including the mass of SUS wire mesh (2) - mass of substrate (4) - mass of SUS wire mesh (1)) x 100
[0144] <Flame retardant (EN13501-1 ISO11925-2)> Using the above adhesive tape, tests were conducted in accordance with ISO11925-2, an ignition test standard defined in the European building material fire safety standard EN13501-1, and the flame retardancy was evaluated based on the average burning length at that time. An average burning length of 100 mm or less was rated as having good flame retardancy.
[0145] [Table 1]
[0146] As can be seen from the results in Table 1 above, Examples 1 to 4, which are adhesive tapes containing an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent and having an adhesive layer with a gel fraction of 50 to 80%, had excellent flame retardancy with a burning length of 100 mm or less in the EN standard flame retardancy test.
[0147] In contrast, Comparative Example 1, in which the gel fraction was less than 50%, Comparative Example 2, in which the gel fraction exceeded 80%, and Comparative Examples 3 to 9, which contained only an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent, all had a combustion amount exceeding 100 mm in the EN standard flame retardancy test and were therefore poor in flame retardancy. [Industrial Applicability]
[0148] This adhesive tape has excellent flame retardancy, adhesive properties, and ease of tearing by hand, and is particularly excellent as an adhesive tape for construction use, so great expectations are high.
Claims
1. An adhesive tape having an adhesive layer on at least one surface of a substrate, the substrate comprising a flat yarn cloth, the adhesive layer comprising an acrylic resin, an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent, and the adhesive layer having a gel fraction of 50 to 80 mass %.
2. 2. The pressure-sensitive adhesive tape according to claim 1, wherein the acrylic resin contains a carboxyl group-containing monomer unit as a monomer unit thereof.
3. 3. The pressure-sensitive adhesive tape according to claim 1, wherein the acrylic resin contains, as a monomer unit, a terminal carboxyl group-containing monomer unit represented by the following general formula (1): 【Chemistry 1】 Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.
4. The pressure-sensitive adhesive tape according to any one of claims 1 to 3, wherein the acrylic resin contains a hydroxyl group-containing monomer unit as a monomer unit thereof.
5. The pressure-sensitive adhesive tape according to any one of claims 1 to 4, wherein the pressure-sensitive adhesive layer contains less than 10 parts by mass of a flame retardant per 100 parts by mass of the acrylic resin.
6. The pressure-sensitive adhesive tape according to any one of claims 1 to 5, wherein the pressure-sensitive adhesive layer contains a tackifier.
7. The pressure-sensitive adhesive tape according to any one of claims 1 to 6, which has a burning length of 100 mm or less in an ignition test according to EN13501-1, the European fire safety standard for building materials.
Citation Information
Patent Citations
Adhesion processed sheet and adhesion processed sheet provided with release sheet
JP2005263993A
Pressure sensitive adhesive tape or sheet having reflecting property and / or light blocking property, and liquid crystal display
JP2007254711A
Adhesive tape
JP2013159643A
Double-sided adhesive tape for fastening aircraft components
JP2015143353A
Heat-resistant adhesive tape
JP2017106013A